DNA Barcoding Supports “Color-Pattern’’-Based Species of Stictochironomus from China (Diptera: Chironomidae) - Chao Song; Guanyu Chen; Le Wang; Teng Lei; Xin Qi (Insects, 2024)
The genus Stictochironomus (Diptera: Chironomidae) has an almost worldwide distribution, with more than 30 species. However, species delimitation and identification based on the markings on the wings and legs are controversial and uncertain. In this study, we focused on color patterns to review the adults of the genus from China, and two new species (S. trifuscipes sp. nov. and S. quadrimaculatus sp. nov.) are described and figured. DNA barcodes can accurately separate the two new species with specific color patterns. However, heterospecific individuals form a monophyletic cluster in the phylogeny tree. For example, S. maculipennis (Meigen) and S. pictulus (Meigen), which have a lower interspecific genetic divergence, form a single clade. Sequences with the same species name but with high intraspecific distance form more than one phylogenetic clade, such as S. sticticus (Fabricius) of three clades, S. pictulus of four clades, S. akizukii (Tokunaga) and S. juncaii Qi, Shi, and Wang of two clades, might have potential cryptic species diversity. Species delimitation analysis using ASAP, PTP, and GMYC clearly delineated them as separate species. Consequently, color patterns are a good diagnostic characteristic for species delimitation in Stictochironomus. The distance-based analysis shows that a threshold of 4.5–7.7% is appropriate for species delimitation in Stictochironomus. Additionally, an updated key including color pattern variation for male adults of known Stictochironomus species from China is provided.